2021
DOI: 10.17660/actahortic.2021.1317.20
|View full text |Cite
|
Sign up to set email alerts
|

Wood fiber in pot plant culture; peat replacement up to 50% in volume?

Abstract: Use of peat and coir in horticulture is under pressure because of the negative effects on the environment. Peat harvesting releases CO2 into the atmosphere and changes the wetland ecosystem. Coir production can cause salt pollution in the country of origin as the product has a high salt level and is washed with fresh water before use as a substrate. HydraFiber, a specific wood fibre product was tested as substitute for (part of) peat and coir in professional potting soils. Wood fibre was mixed in 3 volume perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…There has been very little work on the impacts of HydraFiber specifically. Although our finding that HydraFiber was more detrimental to growth runs contrary to one previous study, which indicated no negative impact of HydraFiber on begonia growth (Eveleens et al, 2021), our results are consistent with studies in coconut fiber (Arenas et al, 2002;Meerow, 1994) and wood fiber (Zawadzi nska et al, 2021). Our study had an unbalanced design, with fewer replicates for HydraFiber, due to limited availability of this substrate from the collaborating producer.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…There has been very little work on the impacts of HydraFiber specifically. Although our finding that HydraFiber was more detrimental to growth runs contrary to one previous study, which indicated no negative impact of HydraFiber on begonia growth (Eveleens et al, 2021), our results are consistent with studies in coconut fiber (Arenas et al, 2002;Meerow, 1994) and wood fiber (Zawadzi nska et al, 2021). Our study had an unbalanced design, with fewer replicates for HydraFiber, due to limited availability of this substrate from the collaborating producer.…”
Section: Discussionsupporting
confidence: 86%
“…There are conflicting reports on the plant health impacts of coir, and in many cases it seems that this product can be harmful to crop growth (Arenas et al, 2002;Meerow, 1994). In addition, coir can cause salt pollution as part of production (Eveleens et al, 2021). As an alternative to coir, there is a new woodand bark-based fiber product, HydraFiber, that can be used as a partial substitute for peat or coir (Eveleens et al, 2021).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…B. [37] points out that the addition of 40% and 50% wood fiber to peat reduces the water content by 16% vv −1 and increases the air content of the substrate by the same amount, which indicates that it is more difficult to overwater, but also requires more accurate monitoring of the water content and the state of the nutrients. Wood fiber media needs to be watered more frequently than peat.…”
Section: Discussionmentioning
confidence: 99%